Lung volumes and flow rates in black and white subjects - Lapp, N. L. (1974)
Lapp, N. L., Amandus, H. E., Hall, R., and Morgan, W. K. C. (1974).Thorax, 29, 185-188. Lung volumes and flow rates in black and white subjects. It has been known for some time that the vital capacity and forced expiratory volume in one second of black subjects are about 12% lower than those of whites of the same age and height. In the present study, total lung capacity and residual volume were also shown to be decreased by about the same percentage. Expiratory flow rates were similarly decreased, but when the difference in lung size was evened out by matching black and white subjects of the same total lung capacity, no significant differences in flow rates were observed.